“I started Reading When My Idol is the Character of Story” Study of Motivation to Read English Fanfiction - Dena Restika Dwi Cahyati; Tryanti R Abdulrahman (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This study specifically discusses the motivation make young generations want to read fanfiction in English while in the fact Indonesian fanfiction is as good as English fanfiction. This study will examine how fanfiction can influence people learning English. This study is used a qualitative method The participants of this study consists of five participants. The participants are the ones who’s read English Fanfiction the data will be collected by interview and analyze by using qualitative method. The interview will be conducted via email for 30 minutes per person. This study mention gender, age, and fandom for the data.